The Cortical Response Evoked by Robotic Wrist Perturbations Reflects Level of Proprioceptive Impairment After Stroke - van Kordelaar, Joost; van de Ruit, Mark; Solis-Escalante, Teodoro; Aerden, Leo A. M.; Meskers, Carel G. M.; van Wegen, Erwin E. H.; Schouten, Alfred C.; Kwakkel, Gert; van der Helm, Frans C. T. (Frontiers in Human Neuroscience, 2021)
Background Proprioception is important for regaining motor function in the paretic upper extremity after stroke. However, clinical assessments of proprioception are subjective and require verbal responses from the patient to applied proprioceptive stimuli. Cortical responses evoked by robotic wrist perturbations and measured by electroencephalography (EEG) may be an objective method to support current clinical assessments of proprioception. Objective To establish whether evoked cortical responses reflect proprioceptive deficits as assessed by clinical scales and whether they predict upper extremity motor function at 26 weeks after stroke. Methods Thirty-one patients with stroke were included. In week 1, 3, 5, 12 and 26 after stroke, the upper extremity sections of the Erasmus modified Nottingham Sensory Assessment (EmNSA-UE) and the Fugl-Meyer Motor Assessment (FM-UE) and the EEG responses (64 channels) to robotic wrist perturbations were measured. The extent to which proprioceptive input was conveyed to the affected hemisphere was estimated by the signal-to-noise ratio (SNR) of the evoked response. The relationships between SNR and EmNSA-UE as well as SNR and time after stroke were investigated using linear regression. Receiver-operating-characteristic curves were used to compare the predictive values of SNR and EmNSA-UE for predicting whether patients regained some selective motor control (FM-UE˃22) or whether they could only move their paretic upper extremity within basic limb synergies (FM-UE≤22) at 26 weeks after stroke. Results Patients (N=7) with impaired proprioception (EmNSA-UE proprioception score<8) had significantly smaller SNR than patients with unimpaired proprioception (N=24) (EmNSA-UE proprioception score = 8, t(29)=2.36, p=0.03). No significant effect of time after stroke on SNR was observed. Furthermore, there was no significant difference in the predictive value between EmNSA-UE and SNR for predicting motor function at 26 weeks after stroke. Conclusions The SNR of the evoked cortical response does not significantly change as a function of time after stroke and differs between patients with clinically assessed impaired and unimpaired proprioception, suggesting that SNR reflects persistent damage to proprioceptive pathways. A similar predictive value with respect to EmNSA-UE suggests that SNR may be used as an objective predictor next to clinical sensory assessments for predicting motor function at 26 weeks after stroke.